Relevant methane emission to the atmosphere from a geological gas manifestation - Mazzini, Adriano; Sciarra, Alessandra; Etiope, Giuseppe; Sadavarte, Pankaj; Houweling, Sander; Pandey, Sudhanshu; Husein, Alwi (Scientific Reports, 2021)
Quantifying natural geological sources of methane (CH4) allows to improve the assessment of anthropogenic emissions to the atmosphere from fossil fuel industries. The global CH4 flux of geological gas is, however, an object of debate. Recent fossil (14C-free) CH4 measurements in preindustrial-era ice cores suggest very low global geological emissions (~ 1.6 Tg year-1), implying a larger fossil fuel industry source. This is however in contrast with previously published bottom-up and top-down geo-emission estimates (~ 45 Tg year-1) and even regional-scale emissions of ~ 1-2 Tg year-1. Here we report on significant geological CH4 emissions from the Lusi hydrothermal system (Indonesia), measured by ground-based and satellite (TROPOMI) techniques. Both techniques indicate a total CH4 output of ~ 0.1 Tg year-1, equivalent to the minimum value of global geo-emission derived by ice core 14CH4 estimates. Our results are consistent with the order of magnitude of the emission factors of large seeps used in global bottom-up estimates, and endorse a substantial contribution from natural Earth's CH4 degassing. The preindustrial ice core assessments of geological CH4 release may be underestimated and require further study. Satellite measurements can help to test geological CH4 emission factors and explain the gap between the contrasting estimates. Published 4138 6A. Geochimica per l'ambiente e geologia medica JCR Journal